2022
DOI: 10.3389/fonc.2022.837248
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of hnRNPA1 Promotes NSCLC Metastasis and EMT by Regulating Alternative Splicing of LAS1L exon 9

Abstract: Tumor metastasis is still an insurmountable obstacle in tumor treatment. Lung cancer represents one of the most common malignancies with high morbidity worldwide. hnRNPA1 has been reported to be involved in the regulation of tumor metastasis, while its specific role in tumor metastasis seems to be controversial and its molecular mechanism in lung cancer metastasis remains to be further elucidated. In this study, we confirmed that knockdown of the hnRNPA1 led to enhanced migration, invasion and EMT transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, although several studies have shown that hnRNPA1 can inhibit tumor proliferation and metastasis [ 43 , 46 , 66 68 ] and that hnRNPA1 may act as an antitumor factor during tumorigenesis, other studies have reached the opposite conclusion [ 69 72 ]. However, in the present study, hnRNPA1 knockdown promoted the growth of AGS and Kato III cells in a manner dependent on the formation of RONΔ160.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although several studies have shown that hnRNPA1 can inhibit tumor proliferation and metastasis [ 43 , 46 , 66 68 ] and that hnRNPA1 may act as an antitumor factor during tumorigenesis, other studies have reached the opposite conclusion [ 69 72 ]. However, in the present study, hnRNPA1 knockdown promoted the growth of AGS and Kato III cells in a manner dependent on the formation of RONΔ160.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different reports on the regulatory role of hnRNPA1 in A549 cells have been published. Liu et al reported that hnRNPA1 knockdown inhibited A549 cell growth through cell cycle arrest [ 80 ], and Han et al reported that hnRNPA1 knockdown significantly promoted EMT progression and the metastatic ability of A549 cells through the regulation of alternative splicing via the LAS1L exon 9 skipping event [ 68 ]. It is suggested that hnRNPA1 plays different roles in cancer cells even within the same organ, which is dependent on mRNA splicing.…”
Section: Discussionmentioning
confidence: 99%
“…HnRNP induce tumor migration and metastasis through AS ( Figure 3 ). HnRNPA1 enhanced lung cancer metastasis by modulating the splicing of LAS1L exon 9 [ 134 ]. HnRNPA2/B1-induced AS of TP53INP2 inhibited migration in ovarian cancer cell lines [ 101 ].…”
Section: Role Of Hnrnp In Cancermentioning
confidence: 99%
“…For example, hnRNPA1's interaction with the flanking exon 9 of PKM leads to an increased skipping of exon 9 and the subsequent up‐regulation of the PKM2 isoform lacking exon 9 77 . However, hnRNPs can also inhibit exon exclusion when binding to exonic regions 78 . Furthermore, SR proteins and hnRNP proteins exhibit antagonistic activities, either promoting or inhibiting splicing 79 .…”
Section: Alternative Splicingmentioning
confidence: 99%
“… 77 However, hnRNPs can also inhibit exon exclusion when binding to exonic regions. 78 Furthermore, SR proteins and hnRNP proteins exhibit antagonistic activities, either promoting or inhibiting splicing. 79 Consequently, modulation of the balance between SR and hnRNP proteins can impact alternative splicing in nuclear speckles.…”
Section: Alternative Splicingmentioning
confidence: 99%